Influência do manuseio neonatal sobre a preferência de ratos jovens por drogas psicoestimulantes - Antoniazzi, Caren Tatiane de David (2012)
The abusive use of psychostimulant drugs is a common social problem in countries of different cultures, whose incidence is increasing and alarming dimensions taken. Experimentally, some studies have shown the influence of early exposure to stress on changes in patterns of abuse, which may play an important role on the vulnerability to excessive use of psychostimulant drugs in adulthood. On the other hand, procedures such as neonatal tactile stimulation (TS) and neonatal isolation (NI), has been described by interfering with behavioral and neurophysiological parameters, which may persist into adulthood. This study aimed to investigate the conditioned place preference (CPP) and the psychostimulant drugs on anxiety-like symptoms related to abstinence in young rats exposed to TS and NI. In the first experiment, male pups of Wistar rats were subjected daily to TS or NI10 for 10 minutes, or NI60 for 1 hour, from postnatal day 1 (PND1) to PND21. The unhandled (UH) animals remained in the nest without any manipulation. At PND41, animals were subjected to CPP protocol induced by cocaine (20mg/kg, i.p.), for 10 days. At PND53, animals were tested for preference, and at PND55 symptoms of anxiety were evaluated on the elevated plus-maze task (EPM). TS and NI10 groups did not show preference on CPP, however UH and NI60 preferred the chamber associated with drug. In relation to anxiety-like symptoms observed during drug withdrawal, TS and NI10 groups presented higher time spent in the open arms of EPM, showing less anxiety-like behavior. Following the first study, a 2nd experiment was conducted to verify the influence of TS and NI on the CPP induced by amphetamine (AMPH), following the same neonatal handling protocol described in the previous experiment until the PND40, when animals were submitted to a CPP paradigm associated with administration of AMPH (4mg/kg, i.p.) for 8 days. At PND50, following behavioral assessment was observed that NI group had preference for the compartment associated with AMPH, and at PND53 during withdrawal of drug, TS group showed lower preference to compartment associated with drug. The exploratory activity in open field was higher in TS group at PND50, while NI group showed anxiety-like symptoms at PND53. Similarly, animals exposed to TS showed lesser degree of anxiety-like behavior in many different parameters evaluated at EPM and at staircase test, where the exploratory activity also was higher than other handlings. Taken together, these studies showed for the first time that beneficial effects of TS can modify the behavior on CPP paradigm, and influence the anxiety-like symptoms related to withdrawal from cocaine and AMPH. Continuity of studies related to the benefits of TS on reward pathways, neurotransmitter systems and signaling pathways, should be completed in the near future.